1998
DOI: 10.1128/aac.42.3.631
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and Pharmacokinetic Interactions of Rifabutin and Clarithromycin in Human Immunodeficiency Virus-Infected Volunteers

Abstract: This study evaluated the tolerance and potential pharmacokinetic interactions between clarithromycin (500 mg every 12 h) and rifabutin (300 mg daily) in clinically stable human immunodeficiency virus-infected volunteers with CD4 counts of <200 cells/mm 3 . Thirty-four subjects were randomized equally to either regimen A or regimen B. On days 1 to 14, subjects assigned to regimen A received clarithromycin and subjects assigned to regimen B received rifabutin, and then both groups received both drugs on days 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 37 publications
2
34
1
Order By: Relevance
“…The relative contribution of rifabutin or the desacetyl-rifabutin metabolite (or other metabolites not measured here) to rifabutin-associated adverse drug reactions is not clear [2,12,19]. It is clear that exposure to the metabolite increases after the addition of lopinavir-ritonavir.…”
Section: Discussionmentioning
confidence: 97%
“…The relative contribution of rifabutin or the desacetyl-rifabutin metabolite (or other metabolites not measured here) to rifabutin-associated adverse drug reactions is not clear [2,12,19]. It is clear that exposure to the metabolite increases after the addition of lopinavir-ritonavir.…”
Section: Discussionmentioning
confidence: 97%
“…In this light, to uncover new advances in the treatment of opportunistic disease remains an important priority for HIV research. Although clarithromycin remains a well-established component of effective therapy for treatment of disseminated MAC, there remain clinically relevant concerns regarding its use [5,8,25]. On the basis of the collection of analyses performed on the data from this trial, azithromycin 600 mg taken every day, when given in combination with ethambutol, is an effective agent for the treatment of disseminated M. avium disease in HIV-infected patients.…”
Section: Discussionmentioning
confidence: 98%
“…A particular role for rifabutin has been noted in patients with proven evidence of Mycobacterium avium infection, although this was not the case in this subject[9]. Previous studies reported pharmacokinetic interactions when combining rifabutin and clarithromycin leading to an increase in rifabutin levels, resulting in an increase frequency of uveitis, this could explain the acute onset of uveitis in our case[10]. …”
Section: Discussionmentioning
confidence: 64%